Jerome of Stridon and the femenine ideal in the treaty against Helvidius: on the perpetual virginity of blessed Mary - Leitón Redondo, Andrea (2023)
This paper makes an analysis of the feminine ideal in a apologetic work by Jerome of Stridon, in which the author defends the virginity of Mary, the mother of Jesus of Nazareth. The proposal of Jerome of Stridon seeks to position the religious movement in the midst of fierce adversary attacks, exhorting women to imitate the Marian figure, since she is the model that Christianity requires and which they must follow to please the divine.